Spiritual Music Relaxation for Pregnant Mother with Preeclampsia in Puskesmas Gajahan Surakarta - Endang Sri Wahyuni; Lely Firrahmawati; Irvina Nurul Mahmudah; Ai Rahmawati; Juleha Duwi Handayani; Anindya Kusuma Wardani Widharna; Renata Fina Antika Cahyani (MEDICAL JURNAL OF AL-QODIRI, 2025)
Background: Preeclampsia is the leading cause of maternal mortality in Indonesia. Music encompasses both material and spiritual dimensions, integrating physical and spiritual components. Techniques for relaxation that incorporate belief systems are thought to alleviate anxiety and potentially lower blood pressure. This study aims to explore the effects of spiritual relaxation through music on pregnant women suffering from preeclampsia at the Gajahan Health Center in Surakarta. Methods: The research was conducted with a Pre-Experimental Design and One-Group Pretest-Posttest Design. Researchers conducted an initial test (pretest) before treatment, and measurements were taken again after treatment (posttest). The subjects of this study were pregnant women who were diagnosed with preeclampsia at the Gajahan Health Center in Surakarta. Music spiritual relaxation therapy is carried out every day for 7 days using audio guides, as well as assistance from the research team. Results: The average blood pressure of pre-eclampsia pregnant women before the spiritual relaxation music therapy treatment was 145/84 mmHg. The average blood pressure of pre-eclampsia pregnant women after spiritual relaxation music therapy treatment is 129/79. The average HARS scale for pregnant women with pre-eclampsia before treatment was 12, and after treatment was 7,8. The response of pre-eclampsia pregnant women before being treated was fear and anxiety, after the spiritual music therapy relaxation treatment, the mother stated that she felt relaxed, calm, and comfortable. Conclusion: The blood pressure of pregnant women with preeclampsia decreased after doing music spiritual relaxation therapy.